(untitled) (Proceedings of the International Conference on Social Sciences, 2023)
Green management initiatives are now a significant factor in forward-thinking tertiary educational institutions around the world and Africa as a way of tackling environmental degradation. Industrialisation has contributed to the global environmental problems facing organisations in terms of sustainability therefore green human resource management activities such as green recruitment and selection have become relevant in the mitigation of climate change actions in the tertiary education industry. While the standing of green recruitment and selection in environmental workforce management has been extensively recognised, there are limited studies on the effect of green recruitment and selection on employee work performance, therefore this study evaluates the effect of green recruitment and selection on employee work performance at Uni4online Westville Durban, Republic of South Africa. The following are the objectives (1) determine employee environmental awareness, and (2) establish the influence of green recruitment and selection on employee work performance The study followed a quantitative research approach and a questionnaire with (15) Likert 5.0 questions was used to collect data from (n=100) employees of the specific Uni4online, Westville Durban South Africa. With a confidence level of 95% and a population size of 142 employees, a margin of error fixed at 5% a qualtric sample size calculator was used to determine the sample for the study. Data were analysed with a descriptive statistical method using SPSS version 26. For sampling purposes, the simple random positivist sampling method was used. The results of the survey confirmed that green recruitment and selection have a positive impact on employee job performance, especially concerning environmental awareness and social-ecological awareness. The study recommends that Uni4online, Durban Republic of South Africa should prioritize green recruitment and selection practices that, when well-planned and applied green recruitment and selection improve employee environmental awareness and behaviour and contribute to enticing more competent job candidates. The study equally revealed a direct correlation between green recruitment and selection and employee work performance, especially within the tertiary education industry.